ANALISIS PENERAPAN PERNYATAAN STANDAR AKUNTANSI KEUANGAN (PSAK) NO. 14 DALAM METODE PENCATATAN DAN PENILAIAN PERSEDIAAN BARANG DAGANG(Studi Kasus: Toko Sabang Merauke Mart Ampek Angkek) - Divira Rintacha; Santi Deswita; Tartila Devy; Novera Martilova (CV. ADIBA AISHA AMIRA, 2026)
Accurate inventory recording and valuation plays a crucial role in the preparation of financial statements, as errors at this stage can affect the calculation of cost of goods sold, profit, and the value of current assets presented in the balance sheet. Accurate inventory information is crucial for both internal and external stakeholders in the economic decision-making process. Therefore, Financial Accounting Standards (PSAK) No. 14 serves as a reference to ensure that all inventory recording, measurement, and reporting activities are carried out consistently, transparently, and verifiably. This study uses a descriptive qualitative approach with data collection techniques including interviews, observations, and field documentation at Sabang Marauke Mart. The analysis stages include data reduction, presentation of results, and drawing conclusions to obtain a true picture of the application of Public Sector Accounting Standards (PSAK) No. 14 in the company's inventory accounting system. The results show that Sabang Marauke Mart uses the periodic (physical) recording method and the FIFO (first-in, first-out) valuation method. Although this implementation is in accordance with PSAK No. 14 guidelines, its effectiveness is not optimal, because the recording process is still done manually and has not been digitally integrated. The lack of human resources with in-depth knowledge of accounting standards is also a factor inhibiting the optimization of the implementation of this system.